1997
DOI: 10.1159/000291818
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological Symptoms and Vaginal Wet Smear Findings in Women with Cervical Human Papillomavirus Infection

Abstract: Objectives: To investigate the signs, symptoms and changes in the vaginal milieu that could be associated with cervical human papillomavirus infection (CHPI). Study design: Women (n = 972) attending for contraceptive advice were tested for human papillomavirus in cervical samples. Results of gynecological history, examination, and vaginal wet smear findings were compared between CHPI patients and negative women. Results: Sixty-six (6.8%) of the women had a CHPI. Bacterial vaginosis was more common among those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…The case-control study by Castle et al [10] found no significant association between BV and HPV. In contrast, a significant association was observed by Sikstrom et al [11], which may be due to sexual behavior factors. We found a statistically significantly greater proportion of BV in pregnant women with HPV compared to pregnant women without HPV.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The case-control study by Castle et al [10] found no significant association between BV and HPV. In contrast, a significant association was observed by Sikstrom et al [11], which may be due to sexual behavior factors. We found a statistically significantly greater proportion of BV in pregnant women with HPV compared to pregnant women without HPV.…”
Section: Discussionmentioning
confidence: 71%
“…We found a statistically significantly greater proportion of BV in pregnant women with HPV compared to pregnant women without HPV. Infection by HPV when BV is active may be facilitated by the presence of products derived from this abnormal microflora, such as sialidase enzymes, and the presence of amines [11]. Briselden et al [16] have demonstrated positivity for such enzymes in 84% of women with BV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, women with other conditions, apart from trichomoniasis, e.g. those infected by human papillomavirus, may present a fishy odor as registered by the examiner 14 . In a test of men exposed to anaerobic culture plates with isolates of the vaginal fluid, it was generally experienced as an unpleasant odor, although some reported that the smell appealed to them (E. Holst, unpublished observations).…”
Section: B a C T E R I A L V A G I N O S I S I S A C R U D E D I A G mentioning
confidence: 99%
“…There are indications of an association between human papillomavirus infection and bacterial vaginosis 14 . It is, however, unclear whether bacterial vaginosis or the human papillomavirus infection is 'the chicken' or 'the egg' in promoting the other.…”
Section: I C R O B I O L O G I C a L M A R K E R S O T H E R T H A mentioning
confidence: 99%